Leadership style index in Malaysian halal small and medium enterprises - Azizan, S.A.; Wan Mohamed Radzi, C.W.J.; Manap, N.A.; Jenatabadi, H.S. (2017)
Manufacturing in halalfood industry world is today extremely competitive. The only attempt to continue is to adjust the needs tofind the good leading ways of changing. Leaders in halal food companies must highlight actions to make changes as rapidly and easily as possible. Halal food has its own perception of food processes which have been seriously considerable for Muslim people. Therefore, in halal business and manufacturing we should have extremely committed and flexible leaders and workers. Of course, principals' leadership methods and decision making can effect on company development. This paper investigated to find the most important factors of leadership style in small and medium enterprises (SME) in halal food industry, Malaysia. The data has been analyzed based on descriptive statistic (frequency table, mean, standard deviation, and etc.) and inferential statistics (includes Cronbach' Alpha Coefficient and independent two sample t-test).